2018
DOI: 10.1063/1.5010402
|View full text |Cite
|
Sign up to set email alerts
|

Semiclassical fluid model of nonlinear plasmons in doped graphene

Abstract: A nonlinear fluid model of high-frequency plasmons in doped graphene is derived by taking fluid moments of the semi-classical kinetic equation for the electron gas. As a closure of the fluid moments, adiabatic compression is assumed with a given form of the distribution function, combined with an exact linear response based on the linearized Vlasov-Poisson system. In the linear regime, the model is in the long wavelength limit consistent with previous results using the random phase approximation for a two-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…Here, the transport parameters [19] are related to the coefficients of f 1 . The change in the energy state is defined by the change in Fermi levels, which generates conductivity [52]. We put the values of f (equation ( 11)) in the equation ( 9)…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Here, the transport parameters [19] are related to the coefficients of f 1 . The change in the energy state is defined by the change in Fermi levels, which generates conductivity [52]. We put the values of f (equation ( 11)) in the equation ( 9)…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…For the typical experimental values ε r = 2.5 and n 0 ∈ [5 × 10 −3 , 1] × 10 12 cm −2 , ω p lies in the THz-region, ω p ∈ [2.6, 37.3] THz. The first term ω ∼ √ q describes the long wavelength signature of plasmons in twodimensional electron gases (2DEG) [36][37][38][39]. The most notable difference, when compared to the characteristic plasmon frequency in the 3-dimensional parabolic case, ω 3D p = e 2 n 0 /(ε 0 ε r m), is the appearance of in leading order, revealing its pure quantum nature.…”
Section: Wigner Formalismmentioning
confidence: 99%
“…In a typical material this can happen only at extremly large optical intensities so there is a constant search for materials with nonlinear response at low intensities. Recently there was a lot of interest in the nonlinear response of plasmons in graphene [5][6][7][8][9][10][11][12][13][14][15][16][17]. Particularly it was shown that graphene has a strong nonlinear response in the form of multiplasmon absorption at very low intensities [7].…”
mentioning
confidence: 99%